Association of Lifestyle Determinants with Coronary Artery Disease (Medical Forum Monthly, 2020)
Objective: The present study examined the association of dietary patterns, smoking and physical activity with Coronary artery disease.Study Design: A case-control studyPlace and Duration of Study: This study was conducted at the Ayub Teaching Hospital, Abbottabad from January 2017 to January 2018.Materials and Methods: The total sample size was 360, of whom 120 were cases and 240 were controls matched for gender and age ±5 years. Non-probability convenient sampling technique was followed in sample selection. The data on dietary patterns, smoking and physical activity was collected with the help of a structured questionnaire and analyzed using Statistical Package for the Social Sciences software.Results: For the sample of 360, the mean age was 58.79 ± 13.356 and included 198 males and 162 females. The results showed that decreased number of cigarettes (OR: 0.889; 95% CI: 0.125-6.310), higher fruit consumption frequency (OR: 1.495, 95% CI 0.696-3.214) and physical activity (OR: 1.495, 95% CI 0.696-3.214) play a protective role in patients of CHD, while vegetable intake (OR: 1.181, 95% CI 0.529-2.637) and duration of exercise (OR: 0.933; 95% CI: 0.111-7.820) had insignificant role.Conclusion: There is association of smoking, physical activity and fruit consumption with CAD, however vegetable intake is not associated with CAD.